COVID-19 and its main oral manifestations - Gonzalez, Caroline Brum; Charone, Senda; Carvalho, Elizeu Fagundes de; Groisman, Sonia (Seven Editora, 2023)
In December 2019, the global spread of a new virus known as SARS-CoV-2, which is responsible for the disease called COVID-19, occurred, triggering an unprecedented crisis around the world. On March 11, 2020, the World Health Organization (WHO) declared the situation a pandemic. As of June 16, 2020, there have been more than 7.9 million confirmed cases and 434,796 deaths in more than 200 countries. Brazil was the second most affected country, with more than 900,000 confirmed cases and 43,332 deaths. DOI:https://doi.org/10.56238/emerrelcovid19-064